2005
DOI: 10.2139/ssrn.666481
|View full text |Cite
|
Sign up to set email alerts
|

Jurisdictional Competition for Trust Funds: An Empirical Analysis of Perpetuities and Taxes

Abstract: abstract. This Article presents the first empirical study of the domestic jurisdictional competition for trust funds. To allow donors to exploit a loophole in the federal estate tax, since 1986 a host of states have abolished the Rule Against Perpetuities as applied to interests in trust. To allow individuals to shield assets from creditors, since 1997 a handful of states have validated self-settled asset protection trusts. Based on reports to federal banking authorities, we find that, on average, through 2003… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…652-54). Third, as a result of the jurisdictional competition for trust funds, state laws concerning the rule against perpetuities and self-settled asset protection trusts became significantly differentiated beginning in 1997 (see Sitkoff and Schanzenbach 2005). 30 Although these changes do not bear directly on trust investment law, they nonetheless have the potential to affect trust investment practice.…”
Section: Datamentioning
confidence: 99%
“…652-54). Third, as a result of the jurisdictional competition for trust funds, state laws concerning the rule against perpetuities and self-settled asset protection trusts became significantly differentiated beginning in 1997 (see Sitkoff and Schanzenbach 2005). 30 Although these changes do not bear directly on trust investment law, they nonetheless have the potential to affect trust investment practice.…”
Section: Datamentioning
confidence: 99%
“…Beginning in the late 1990s, state trust laws became significantly differentiated on a handful of margins in response to lobbying by local bankers and lawyers, who sought to attract out-of-state trust business. In Sitkoff and Schanzenbach (2005), we found that certain of these reforms were associated with substantial increases in reported trust assets and average account size. 20 Accordingly, in some specifications we undertake national-level analysis, cut the data in 1997, 21 or control directly for these reforms (as well as principal-and-income reform).…”
Section: A the Fdic Datamentioning
confidence: 82%
“…§ 1811), was enacted in 1994 but the reform at issue did not take effect until 1997. 20 The principal effect was in states that authorized perpetual trusts and did not levy a fiduciary income tax (Sitkoff and Schanzenbach [2005], pp. 410-11).…”
Section: A the Fdic Datamentioning
confidence: 99%
See 2 more Smart Citations